Six nights of seduction - Child, Maureen (Harlequin desire, 2021)
"From invisible assistant...to irresistible siren! She's crossed the line. For Tessa Parker, the most intoxicating thing about working at premium vodka producer Graystone Spirits is her off-limits boss. Yet she's never gotten CEO Noah Graystone to see her as anything but his loyal assistant. Finally fed up enough to tender her resignation, she agrees to one last business trip to London together--and seizes her chance for a no-strings-attached seduction! But is their steamy six-day fling the last call?"-- Page [4] of cover.